2012
DOI: 10.1503/cjs.033910
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lifetime incremental cost:utility ratios of surgery relative to failed medical management for the treatment of hip, knee and spine osteoarthritis modelled using 2-year postsurgical values

Abstract: Comparison of lifetime incremental cost:utility ratios of surgery relative to failed medical management for the treatment of hip, knee and spine osteoarthritis modelled using 2-year postsurgical values Background: Demand for surgery to treat osteoarthritis (OA) of the hip, knee and spine has risen dramatically. Whereas total hip (THA) and total knee arthroplasty (TKA) have been widely accepted as cost-effective, spine surgeries (decompression, decompression with fusion) to treat degenerative conditions remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 40 publications
(61 reference statements)
2
48
0
1
Order By: Relevance
“…For example, Tso et al [8] used SF-6D to convert physical and mental outcome data into utility scores after THA, TKA, and lumbar decompressions. They determined QALYs gained for each procedure and concluded that incremental cost:utility ratio per QALY for each cohort was $5321, $11,275, and $2307 for THA, TKA, and spinal decompression, surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tso et al [8] used SF-6D to convert physical and mental outcome data into utility scores after THA, TKA, and lumbar decompressions. They determined QALYs gained for each procedure and concluded that incremental cost:utility ratio per QALY for each cohort was $5321, $11,275, and $2307 for THA, TKA, and spinal decompression, surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The short form 6D is a relatively new measurement method, and several studies have used it to derive cost-utility ratios to compare outcomes of different surgical interventions to each other as well as to medical management alone [7,8]. This score is of interest as it provides a description of health and has the capability to be used in an economic model.…”
mentioning
confidence: 99%
“…Due to the wide time frame in which clinical research was conducted, the various study designs, and the case groups that were evaluated, we find that many evaluations of medical interventions, which are based on health economics principles, are being developed for aspects of orthopedic surgery that range from surgical therapy to pharmacotherapy or disease prevention [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Examples Of Health Economics Value In Orthopedic Surgerymentioning
confidence: 99%
“…[7] For example, primary total hip arthroplasty (THA) and total knee arthroplasty (TKA) have proven to be among the most cost-effective surgical interventions both musculoskeletal and otherwise at $8031 per QALY for THA and $18,300 per QALY for TKA. [25]…”
Section: Definition Of Quality Adjusted Life Yearmentioning
confidence: 99%
“…This enables the comparison of ICURs for the treatment of multiple conditions. [25] Our primary objective in this review was to assess the improved health vs. maintained-related quality of life (QALY) for those undergoing decompression with interbody fusion accompanied by bone morphogenetic protein (BMP) for spinal stenosis with degenerative spondylolisthesis (DS) vs. more routine posterolateral fusion (PLF) techniques without BMP.…”
Section: Introductionmentioning
confidence: 99%